Sustainability Accounting Practices and Reporting Differences among Key Sub-industrial Players in the Environmentally Sensitive Industry in Sub-Sahara Africa - Penney, Emmanuel Kofi; Lamptey, Lazarus Lanquaye; Amoh, John Kwaku; Aboagye, Alice Anima; Sampson, Vivian Esumanba (International Journal of Economics and Financial Issues, 2025)
In response to claims that environmentally sensitive industries (ESI) fail in sustainable development but rather damage the economy, environment and societal well-being, this paper demonstrates how, in Sub-Saharan Africa, ESI subsectors differ in sustainability practises and decompose the differences in the lenses of Institutional isomorphism theory. Using non-parametric techniques and sampling from Sub-Saharan African stock markets, the study detects a significant difference. The empirical results showed that mining firms show relatively exceptional sustainability reporting performance and suggest institutional issues should be considered when analysing subsectors. The significant disparities between the mining subsector and the other two subsectors are due to environmental sensitivity, sectorial institutional independence, and social actor impact. The findings support the necessity to exercise care when cautioning sustainable development behaviours of distinct groups in the ESI.